2017
DOI: 10.1111/1751-2980.12506
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of non‐invasive multi‐slice spiral computed tomography‐based indices for the diagnosis and prognosis prediction of liver cirrhosis

Abstract: The easily available parameters of CT can accurately evaluate the severity of cirrhosis in Chinese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Several studies using CT and MRI have shown that volumetric analysis of the liver and spleen can be used to differentiate between cirrhotic and non-cirrhotic livers (Supplementary Table 1 ) [ 22 , 34 , 36 , 49 , 51 , 67 69 ]. Torres et al in 1986 reported on morphological volume changes of hepatic segments using CT images of 75 biopsy-proven cirrhotic and 50 control patients with no liver disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using CT and MRI have shown that volumetric analysis of the liver and spleen can be used to differentiate between cirrhotic and non-cirrhotic livers (Supplementary Table 1 ) [ 22 , 34 , 36 , 49 , 51 , 67 69 ]. Torres et al in 1986 reported on morphological volume changes of hepatic segments using CT images of 75 biopsy-proven cirrhotic and 50 control patients with no liver disease.…”
Section: Methodsmentioning
confidence: 99%
“…This is evidenced by data from a large cohort from the United States of 8853 patients undergoing CT colonography or CT for renal donor work-up whereby the mean spleen volume for males and females was 216 ± 100 cm 3 [39]. A summary of studies reporting normal spleen volumes is provided in Supplementary Table 7 [22,24,31,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Such countryspecific thresholds for normal splenic volume remain below the reported splenic volumes for CLD patients with no hepatic fibrosis (Table 2).…”
Section: Thresholds and Normal Rangesmentioning
confidence: 99%